NATURAL REGENERATION CHARACTERISTICS OF TROPICAL EVERGREEN MOIST CLOSE FOREST IN TAN PHU AREA OF DONG NAI PROVINCE - Van Long, Le; Thi Tuyen, Phung; Ba Toan, Le; Xuan Quy, Pham (Journal of Forestry Science and Technology, 2018)
This study was conducted from 2015 to 2017 to determine the natural regeneration characteristics of six plant communities of tropical evergreen moist close forest in Tan Phu area, Dong Nai province. Data were collected from 600 subplots (16 m2) set up in thirty 0.25ha-plots (five 0.25-ha plots/each plant community). The results indicated that, regenerated tree density in study site ranged from 4,595 trees/ha in community Dipterocarpaceae-Elaeocarpaceae-Irvingiaceae (PC5) to 5,815 trees/ha in community Dipterocarpaceae-Myrtaceae-Rosaceae (PC3). The plant community Dipterocarpaceae-Fabaceae-Sapindaceae (PC2) was shown to have the highest number of species (55) among six communites. The similarity coefficient between regenerated trees and mother trees was very high which ranged from 58.3% in community Dipterocarpaceae-Myrtaceae-Rosaceae (PC3) to 96.4% in community Dipterocarpaceae-Rosaceae-Sapindaceae (PC4). Regeneration has been occurring continuously over time and more than 72.5% of regenerated trees had origin from seeds. Regenerated trees with the height > 100 cm were considered as promissing regenerated trees accounted for from 23.9% in community Fabaceae-Ebenaceae-Lythraceae (PC6) to 31.5% in community Dipterocarpaceae-Myrtaceae-Rosaceae (PC3). These regenerated trees can replace mother trees in the future. Base on the natural regeneration characteristics, this study confirm that the study forest will be a sustainable forest dominated by dipterocarpaceae species in the future.